Implementation of Second Step Learning (SSL) as Psychosocial Stimulation of 7-12 Years Old Children with Neglectful Parents - Ika Arum Dewi Satiti; Waifti Amalia (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Parenting style is an important component in children's emotional social development. Children who have parents with the neglectful parenting type tend to be either very aggressive or very passive and aloof so they are at highest risk of getting into various difficulties. The appropriate stimulation needs to be given to children in this condition to improve emotional and social engagement. Second step learning (SSL) is a method of stimulating social emotional development that is used to train empathy skills, emotional management, case solving and socializing. The purpose of this study was to apply the SSL method as psychosocial stimulation for children aged 7-12 years with neglectful parents at SDN Bendosari 2 Pujon, Kabupaten Malang.The research method used is a quasy experiment with data analysis of the dependent T test to see changes in children's psycho-social development before and after the implementation of SSL. Implementation was carried out on 50 children with parents who have a neglectful type of parenting style. The SSL method is carried out in 4 steps, namely material presentation, case discussions, activities with groups and activities with parents. The results of this study indicate a significant change in the mean social emotional values of children before the stimulation of SSL (80.5 ± 11.7) and after stimulation of SSL (90.1 ± 11) with a P value of 0.000. From the results of this study it can be concluded that second step learning (SSL) stimulation is effective in improving the social emotionality of children aged 7-12 years with neglectful parents at SDN Bendosari 2 Pujon, Kabupaten Malang.